Gamow-Teller 1+ states in 112-124Sb isotopes - Çakmak, N.; Ünlü, S.; Selam C. (My University, 2010)
The violated supersymmetry property of the pairing interaction between nucleons were restored using the Pyatov method [Pyatov and Salamov, Nucleonica 22, 127(1977)]. The eigenvalues and eigenfunctions of the restored Hamiltonian with the separable residual Gamow-Teller effective interactions in the particle-hole and particle-particle channels were solved within the framework of proton-neutron quasirandom phase approximation (pnQRPA). The Gamow-Teller resonance energies for 112-124Sb isotopes and the differential cross-sections for Sn(3He, t)Sb reactions at E(3He) = 200 MeV occurring by the excitation of the Gamow-Teller resonance state were calculated. The calculated values were compared with other calculations and the corresponding experimental data. © Indian Academy of Sciences.
Keywords: ?-Decay; Nuclear density functional theory and extensions; Shell model